2019
DOI: 10.1136/bjsports-2019-100669
|View full text |Cite
|
Sign up to set email alerts
|

Recreational and ergogenic substance use and substance use disorders in elite athletes: a narrative review

Abstract: BackgroundSubstances from various classes may be used for recreational purposes, self-treatment or to boost performance. When substance use shifts from occasional to regular, heavy or hazardous use, positive and negative effects can develop that vary by substance class and athlete. Regular use of recreational or performance enhancing substances can lead to misuse, sanctions or use disorders.ObjectiveTo review the prevalence, patterns of use, risk factors, performance effects and types of intervention for all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 128 publications
1
45
1
3
Order By: Relevance
“…Cannabis has the potential to diminish performance due to reducing alertness and reaction time as well as accelerating muscle fatigue (Gil et al 2016). However, studies examining both benefits and adverse effects, as well as knowledge and attitudes, regarding cannabis in adult athletes have been overlooked in favor of studies examining risk (Gil et al 2016;McDuff et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis has the potential to diminish performance due to reducing alertness and reaction time as well as accelerating muscle fatigue (Gil et al 2016). However, studies examining both benefits and adverse effects, as well as knowledge and attitudes, regarding cannabis in adult athletes have been overlooked in favor of studies examining risk (Gil et al 2016;McDuff et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recreational substance use in elite athletes was overshadowed by doping and attracted little scientific attention in the past, but is now researched more intensively. Our review adds to the knowledge of earlier works by including recent studies [7,64]. In our opinion, sports medicine as a cross-sectional subject should integrate knowledge on prevalence rates and treatment options of common mental disorders among elite athletes.…”
Section: Implications For Sports Medicinementioning
confidence: 87%
“…With the exclusion of CBD from the prohibited substances in 2018, and even before, the use of CBD among athletes has considerably increased and is still accelerating ( Leas et al, 2019 ). Cannabinoids are considered the second most commonly used substance among contact sports athletes replacing nicotine ( McDuff et al, 2019 ). Evidence has shown that a third of cyclists, triathletes, and runners are or have been cannabinoids users (mostly ≥ 40 years of age, male, THC + CBD consumers ≤3 times weekly, and exercise 5–7 days per week) ( Zeiger et al, 2019 ).…”
Section: Prevalence In the Use Of Cbd Among Athletesmentioning
confidence: 99%